2016
DOI: 10.1016/j.numecd.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lifestyle interventions on depressive symptoms in individuals at-risk of, or with, type 2 diabetes mellitus: A systematic review and meta-analysis of randomized controlled trials

Abstract: Lifestyle interventions were effective in improving depression among people with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 81 publications
5
30
0
1
Order By: Relevance
“…Study findings showed that the HED-SMART intervention, despite focusing primarily on behavior change, yielded significant benefits by reducing symptoms of depression for both the low stable and high stable groups. This has been shown for self-management programs in other patient group [55]. A similar trend was noted for reduced anxiety, although this failed to reach significance.…”
Section: Discussionsupporting
confidence: 75%
“…Study findings showed that the HED-SMART intervention, despite focusing primarily on behavior change, yielded significant benefits by reducing symptoms of depression for both the low stable and high stable groups. This has been shown for self-management programs in other patient group [55]. A similar trend was noted for reduced anxiety, although this failed to reach significance.…”
Section: Discussionsupporting
confidence: 75%
“…19 HRQoL, mental health, self-efficacy, and self-management outcomes were selected based on effects evidence from T2DM self-management intervention reviews and metaanalyses. [24][25][26] Trained research assistants obtained outcome data at baseline and 6 months after the intervention. Component Summary (MCS).…”
Section: Methodsmentioning
confidence: 99%
“…7 Therapeutic lifestyle changes that target diet and exercise are known to positively influence depressed mood. 34,35 We have previously shown that standard cardiac rehabilitation is effective in not only reducing mortality risk but also in reducing depression symptoms in HF, 7 and that other forms of behavioral interventions favorably affect the somatic/affective but not the cognitive/affective depressive symptoms. 17 Given the elevated IL-6, TNF-R1, and sST2 levels in stage B HF patients with both T2DM and depressed mood, additional attention and interventions to forestall potential transition to symptomatic stage C HF may be warranted.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, depressive symptoms and depressed mood are significant predictors of morbidity and mortality in cardiac and noncardiac populations . Therapeutic lifestyle changes that target diet and exercise are known to positively influence depressed mood . We have previously shown that standard cardiac rehabilitation is effective in not only reducing mortality risk but also in reducing depression symptoms in HF, and that other forms of behavioral interventions favorably affect the somatic/affective but not the cognitive/affective depressive symptoms …”
Section: Discussionmentioning
confidence: 99%